Jombang District Community Perceptions of Women Trainers - Abdul Jabbar Al Baihaqi; Kurniati Rahayuni; Prisca Widiawati (Universitas Riau, 2024)
This reseacrh aims to determine the perception of people in Jombang Regency towards female trainers. This research is motivated by: 1) negative perception and patriarchal culture, where sport is considered only for men and women are considered incapable of success in the field of sport 2) the coaching profession in Indonesia has always been dominated by men, which indicates limited access for women to have coaching experience; 3) social assumptions that lead to discrimination against women who engage in sports activities. This reseacrh used a descriptive quantitative approach, the participants of the reseacrh were the people of Jombang Regency totalling 104 men and 107 women, who used sports infrastructure, could read and write and were adults. This research was conducted by using questionnaires as the validated and disseminated through googleform and pasted information on notice boards in sports venues. This research analysis technique is using descriptive statistics, such as frequency, mean, median, and standard deviation can be used to analyse respondent characteristics, such as age, gender, education level, and level of involvement in sports. The results of this study can be known that 1) external internal barriers, many female trainers often experience fatigue. 2) organizational barriers, government support is still lacking for female trainers. 3) Socio-cultural barriers, the profession of female trainer is a profession that is widely demanded by society to produce achievements. 4) Gender barriers, coach recruitment systems favour men over women.